Pemanfaatan Modul Lora SX1278 Sebagai Sistem Telekontrol pada Robot Penjaga - Wirayudha, Putra; Widiatmoko, Dekki; Sridaryono, Aguk; Syafaat, Mokhammad; Kasiyanto, Kasiyanto (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The frequent armed conflicts in Papua have earned it the dubious distinction of being the number one region in Indonesia with the highest incidence of armed conflicts. These actions are claimed to be the work of the Armed Criminal Group (ACG) and often target military posts or guard stations. Given the conditions at these guard stations, there is a perceived need to introduce technology for better anticipating and countering attacks. In response to these challenges, the author envisions the introduction of a guard robot as a solution. This proposed guard robot is integrated with an SS2 weapon and has the capability for remote control of its firing. The remote control of the robot is facilitated by the LoRa Sx1278 module, which is purported to have a range of up to 500 meters. The researcher's proposed guard robot consists of components, including the Arduino Nano, LoRa SX1278 Module, L298N Motor Driver, DC Motors, Solenoid, 12-Volt LiPo Battery, Step-down module, and KY-023 Joystick. The research findings highlight the impact of the quantity of data on transmission delay. The lowest delay observed during the 10th test, with the transmission of 10 words, had an average delay of 531 ms, while the lowest delay during the first test, involving the transmission of a single word, had an average delay of 81 ms. In terms of data transmission range tests using the LoRa SX1278 module, under Line of Sight (LOS) conditions, the best range achieved was 350 meters, whereas under Non-Line of Sight (NLOS) conditions, the range was limited to 100 meters.